2021
DOI: 10.5267/j.msl.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing business entrepreneurship through open government data

Abstract: Small and medium enterprises play a very important role in today’s economy and contribute heavily on a national economy specially in developing countries like Jordan, but they are still facing many challenges, and need support from government specially in data availability. This study aimed to know the impact of open government data (OGD) on business entrepreneur-ship from Jordanian Irbid State entrepreneurs’ point view. To achieve this, (600) questionnaires were distributed to the sample of Jordanian entrepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In OGD-based entrepreneurial activities, the performance of data demanders in applying government data is subject to a combination of multiple factors, including data quality, timeliness and completeness (Malkawi et al , 2021; Liang et al , 2018; Saxena and Janssen, 2017). According to a survey by Open Data Barometer in 2017, a large amount of government data is not available to the public, so, for instance, only 8% of data could be used for innovation (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In OGD-based entrepreneurial activities, the performance of data demanders in applying government data is subject to a combination of multiple factors, including data quality, timeliness and completeness (Malkawi et al , 2021; Liang et al , 2018; Saxena and Janssen, 2017). According to a survey by Open Data Barometer in 2017, a large amount of government data is not available to the public, so, for instance, only 8% of data could be used for innovation (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since its launch in 2009, Data.gov has established many big data start-ups relying on OGD. An empirical study on Jordanian start-ups also showed that OGD significantly impacts local entrepreneurship (Malkawi et al , 2021). China has the world’s largest and most complex data pool, and the Chinese Government is paying more attention to open data year by year and actively constructing big data resource platforms (Zhang et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proficient leader believes that organizational success can be accomplished only by group work and collaboration with others, allowing opportunities for training and sharpening their skills, and rewarding their performance towards the flourish and progress of the organization. To implement these functions, a leader must be able to apply the behavioral and managerial practices using wise and smart approaches that are based on emotional intelligence, flexible personality traits, and authorization of powers that reflect distinctive individual and institutional performance in general (Malkawi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%